2019
DOI: 10.1016/j.jimonfin.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The divergence of bank lending rates from policy rates after the financial crisis: The role of bank funding costs

Abstract: After the global finance crisis, policy rates were cut to near-zero levels, yet, bank lending rates did not fall as much as the decline in policy rates would have suggested. If the crisis represents a structural break in the relationship between monetary policy and lending rates, how should central banks view the post-crisis transmission? This poses a major puzzle for monetary policymakers. Using a new weighted average cost of liabilities to measure banks' effective funding costs we show a model of interest ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…This study also found that relationship between central banks' policy rate and bank lending rate are proven insignificant. These results have been described in Illes et al (2015) studied reasons why movements in banks' lending rates different with its country's policy rate especially after the crisis. There are three main arguments: (1) policy rate is rather a short-term benchmark rate when compared with a longer tenor of bank loans; (2) banks did not acquire funding at the price of central bank interest rate; and (3) banks tends to face higher funding cost in post-crisis period.…”
Section: Empirical Findingsmentioning
confidence: 75%
“…This study also found that relationship between central banks' policy rate and bank lending rate are proven insignificant. These results have been described in Illes et al (2015) studied reasons why movements in banks' lending rates different with its country's policy rate especially after the crisis. There are three main arguments: (1) policy rate is rather a short-term benchmark rate when compared with a longer tenor of bank loans; (2) banks did not acquire funding at the price of central bank interest rate; and (3) banks tends to face higher funding cost in post-crisis period.…”
Section: Empirical Findingsmentioning
confidence: 75%
“…Nonetheless, the above model may be criticized on the ground that, first, banks are not bound to borrow from the Central bank and pay a penalty rate and, second, developments of bank retail rates do not necessarily reflect the behavior of the policy rate. The policy rate is indeed a very short-term rate, while lending and deposit rates are expected to reflect long-term rates; furthermore, banks may obtain funds from a variety of sources, including retail deposits, interbank, bonds and Treasury bill markets (Illes, Lombardi and Mizen, 2015). Hence, using the policy rate to measure the interest rate pass-through would lead to erroneous conclusion on the interest rate pass-through process.…”
Section: D=r+l-s……………………………………………………………………………mentioning
confidence: 99%
“…By analyzing the cointegration between policy rates and banks' weighted cost of capital, Illes, Lombardi, and Mizen (2019) find that the sensitivity of banks' average funding costs to policy rates has declined in recent years. 5…”
Section: Special Marketmentioning
confidence: 99%